Methicillin-resistant Staphylococcus aureus (MRSA) in slaughtered pigs and abattoir workers in Italy. (October 2015) - Normanno, Giovanni; Dambrosio, Angela; Lorusso, Vanessa; Samoilis, Georgios; Di Taranto, Pietro; Parisi, Antonio
Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a pathogen present in the hospital environment (HA-MRSA), in the community (CA-MRSA) and in livestock, including pigs (LA-MRSA). MRSA may enter the human food chain during slaughtering and may infect humans coming into direct contact with pigs or pork products. This study aimed to determine the prevalence and characteristics of MRSA isolated from pigs and workers at industrial abattoirs in southern Italy. A total of 215 pig nasal swabs were screened for the presence of MRSA using PCR. An MRSA isolate was detected from each mec A/ nuc PCR-positive sample and characterized by spa -typing, Multi-Locus Sequence Typing, SCC- mec and Panton-Valentine Leukocidin (PVL), and also tested for the production of staphylococcal enterotoxins (SEs). Eighty-one MRSA isolates (37.6%) were obtained from the 215 pig nasal swabs; 37 of these isolates were further characterized, and showed 18 different spa -types and 8 different STs. The most frequently recovered STs were ST398 (CC398-t034, t011, t899, t1939 – 43.2%) followed by ST8 (CC8-t008, t064, t2953, t5270 – 24.3%) and ST1 (CC1-t127, t174, t2207 – 10.8%). Nine MRSA isolates were obtained from the 113 human swabs; the isolates showed 5 different spa -types and 5 different STs, including the novel ST2794 (t159). The most representative STs recovered were ST1 (CC1-t127) and ST398 (CC398-t034) (33.3%). None of the MRSA isolates showed the ability to produce SEs and PVL and all resulted resistant to two or more classes of antimicrobials. This study shows the great genetic diversity of MRSA strains in slaughtered pigs and in abattoir employees in Italy, and clearly demonstrates the need for improved hygiene standards to reduce the risk of occupational and food-borne infection linked to the handling/consumption of raw pork containing MRSA. Highlights: Our study shows genetic diversity of MRSA in slaughtered pigs and abattoir workers. A novel Sequence Type (ST2794/t159) was detected. The foodborne risk linked to the consumption of the pork meat appears limited. This is the first report on the prevalence of MRSA in slaughtered pigs in Italy. This is the first report on the prevalence of MRSA in abattoir workers in Italy.